The tourist warming of Tibau/RN: A case study on second residence (Research, Society and Development, 2023)
The study aims to analyze the impact of the second home for tourist heating during the summer period in the municipality of Tibau, in Rio Grande do Norte. The relevance of the study focuses on exposing the impacts caused by the existence of the second residence in the coastal area of ​​Tibau, raising the positive and negative points, the relationship between visitors and inhabitants and the tourist heat. The methodology used was the descriptive/exploratory case study, with qualitative methods, with analysis of the quantitative data collected during the field research and application of the questionnaire. The data will be exposed by graphs, identifying the main points of the questionnaires. Qualitative analysis was carried out based on bibliographical and documental research and field research. With the results, it is clear the relationship between people who live in the city of Tibau with those who go only in free periods, and it was possible to detect the heating of local tourism through the considerable increase in sales of services and products available in the municipality during this period, where the flow of visitors/users of these properties enjoy these services and products, thus contributing to the increase of tourist activity in the locality. However, the research found that despite the continuous presence of the second residence, tourism increases only during the summer season, due to the residents and visitors who occupy these residences. However, for the rest of the year, because these properties remain closed most of the time, the flow is lower and the tourist heat.